Morphological and molecular responses in ovaries of Mytilus galloprovincialis collected in two different sites of the Naples Bay. Issue 1 (24th September 2018) - Rosati, L.; Agnese, M.; Verderame, M.; Aniello, F.; Venditti, M.; Mita, D. G.; Andreuccetti, P.; Prisco, M.
Abstract: Mytilus galloprovincialis female specimens were collected from two mussel farms located in two sites next to Castel dell'Ovo, a historical complex located in the Naples Bay. Such sites were named, respectively, A‐area and B‐area for the different microbiological parameters so that mussels from A‐area can be sold without purification, whereas mussels from B‐area must be purified before sale. The mussels were collected during the nonreproductive (summer 2009) and reproductive periods (autumn 2009). Gonadosomatic index, structural organization of the ovary, presence of apoptosis, estrogen receptors expression, as well as the bisphenol A (BPA) content in the ovaries, were evaluated. Ovaries from specimens collected in area B showed a different and significant distribution of the investigated biomarkers as well as of BPA content in respect to those measured in the A‐area specimens, confirming that mussels are valid sentinel organisms to biomonitor in the Naples bay too. Abstract : Bisphenol A (BPA) content in the Mytilus ovary of samples collected in A‐area and B‐area of Naples Bay. Each value represents the mean ± SEM . Asterisk corresponds to a statistically significant difference ( P < 0.05).